¿Paraíso, mágico y natural? Historia y memorias de la represión política en El Bolsón. 1974-2012 - Ayelén Mereb (Nuevo mundo - Mundos Nuevos, 2017)
The city of El Bolsón, located in the province of Rio Negro, Argentina, is widely known both nationally and internationally as an idyllic, magical and natural community, an image that suits well the intention to mobilize the tourist and real estate market on which the local economy has been routed for the past few decades. The daily social and political rifts are presented, from this perspective, as external to the local community as if they were introduced from outside to disrupt the reigning harmony of the town. However, the city’s history has been marked by conflicts and the successive stigmatization of different identities, while configuring power relationships, citizens’ experiences and their representation.In particular, in relation to our recent history, and due to the town’s relative isolation from the rest of the country, this narrative has led the community’s distance from the political repression of the seventies. This doctoral dissertation seeks to shed light on the different dimensions and modalities of the repression in El Bolsón between 1974 and 1983 digging into the different social memories of these processes that have circulated locally during key moments of the human rights movement since the return to democracy until 2012. That year, the first local memorial directly related with the military dictatorship was created. In order to recount that, I have resorted to protagonists memories, the analysis of diverse documentaries and local and regional media, official documentation, human rights organizations, correspondence, personal archives and other sources that give an account of the recent micro-history of the local social and political conflicts.